Green Lean Concept for Measurement of Sustainable Performance Mediated by Organizational Culture in Oil & Gas and Petrochemical Industry - Santoso, Bambang; Kasih, Tota Pirdo (International Review of Management and Marketing, 2024)
This research explores the measurement of green lean concept in Oil & Gas and Petrochemical Industry in Indonesia to sustainable performance by examine organizational culture as a mediated. The green lean concept approach provides social benefits for industry, financial aspects, and environmental aspects that influence its performance so that it can be sustainable. A structured questionnaire was distributed among employees of the Oil & Gas and Petrochemical Industry in Indonesia. The sample consisted of 153 respondents consisting of 32 female and 121 male, and the composition consisted of Oil & Gas Companies 44 respondents; Oil Companies 87 respondents; and Petrochemical Companies 22 respondents was analyzed using the Structural Equation Modeling - Partial Least Square (SEM-PLS). The results indicate that the green lean concept is proxied by customer relationships, human resource practices, manufacturing planning and control, process and equipment, and supplier relationships have a positive and significant effect on organizational culture in the Oil & Gas and Petrochemical Industry in Indonesia. Organizational culture variable is "Fully Mediating" the sustainable performance variable in the Oil & Gas and Petrochemical Industry in Indonesia. The R-squared value is 65% that green lean concept able to explain, while the remaining 35% explained by other factors that were excluded in this research. The research outcomes contribute to the analysis of the research, broadening the writings on green lean concept and sustainable performance with a mediating of organizational culture. The research possibly will be used as a motivation for industries in Indonesia to implement green lean concept as companies that adopt green lean concept globally have the result of improving firms’ endurable performance through green lean approaches.